Odpowiedzi

Najlepsza Odpowiedź!
2010-04-18T09:55:51+02:00
F(x) = x² + 7x + 11

- 1 = x² + 7x + 11 |+1
0 = x² + 7x + 12
Δ = 49 - 48 = 1*1
x₁ = (- 7 + 1)/2 = - 3
x₂ = (- 7 - 1)/2 = - 4

Funkcja przyjmuje wartość - 1 dla argumentów - 3 i - 4.

f(x) = - 5x² + 3x - 2

- 4 = - 5x² + 3x - 2 |+4
0 = - 5x² + 3x + 2
Δ = 9 + 5*4*2 = 9 + 40 = 7*7
x₁ =(- 3 + 7)/(- 10) = - 0,4
x₂ = (- 3 - 7)/(- 10) = 1

Funkcja przyjmuje wartość - 4 dla argumentów - 0,4 i 1.
jak masz pytania to pisz na pw
2010-04-18T10:14:13+02:00
Zad1.
f(x)=x²+7x+11
-1=x²+7x+11
0=x²+7x+11+1
0=x²+7x+12
Δ=49-4×1×12
Δ=49-48=1
x₁=(-7-1)÷2=-4
x₂=(-7+1)÷2=-3
zad2.
-5x²+3x-2=-4
-5x²+3x+2=0
Δ=9-4×(-5)×2
Δ=9+40
Δ=49
√Δ=7
x₁=(-3-7)÷(-10)=1
x₂=(-3+7)÷(-10)=-⅖